2012
DOI: 10.1007/s10461-012-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Should Home-Based HIV Testing and Counseling Services be Offered Periodically in Programs of ARV Treatment as Prevention? A Case Study in Likoma (Malawi)

Abstract: To reduce HIV incidence, prevention programs centered on the use of antiretrovirals require scaling-up HIV testing and counseling (HTC). Home-based HTC services (HBHTC) increase HTC coverage, but HBHTC has only been evaluated during one-off campaigns. Two years after an initial HBHTC campaign (“round 1”), we conducted another HBHTC campaign (“round 2”) in Likoma (Malawi). HBHTC participation increased during round 2 among women (from 74% to 83%, p<0.01). New HBHTC clients were recruited, especially at ages 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Consistent with previous studies in similar settings 42, 44, uptake of repeat HCT among HIV‐negative individuals was high. Previous HCT may reduce the psychological stress associated with testing hence making it easier to accept repeat HCT.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies in similar settings 42, 44, uptake of repeat HCT among HIV‐negative individuals was high. Previous HCT may reduce the psychological stress associated with testing hence making it easier to accept repeat HCT.…”
Section: Discussionsupporting
confidence: 91%
“…We used data from two home-based HIV testing and counseling campaigns (HTC [66, 67]) to determine the HIV status of each partner in a matched couple. The variable describing HIV status of each partner is coded as infected = 1 versus not infected = 0.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 However, CBHTC programs are delivered through different strategies, and their costs and efficiency in HIV diagnosis vary both between and within specific CBHTC strategies. Prior published estimates of the cost per person tested varied from US$9.6 to $34.7 for mobile CBHTC strategies, 7-13 $5.5 to $18.7 for home-based CBHTC strategies, 11,12,14-18 and $8.3 to $42.0 for venue-based CBHTC strategies that offer HIV testing at convenient locations within the communities (2014 dollars). 8,15,19,20 The costs per person testing HIV positive through CBHTC programs had a wider range from $60.2 to $1725.3, 7-24 which is mainly due to the differences in HIV positivity rate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among the few costing studies that have reported HIV testing coverage, only two included an individual-level census as part of home-based HTC, and achieved 91% testing coverage among all adults 24 and 77% among adults aged 18-35. 14 Other studies reported HIV testing coverage from 26% to 80% based on either estimated number of individuals living in the catchment area 7,10,17 or number of households. 12,18 To reach the UNAIDS 90-90-90 goal, empirical data on the costs of achieving 90% population-level HIV testing coverage are urgently needed.…”
Section: Introductionmentioning
confidence: 99%